New Patent on Electrospinning for Increasing Rutin Loading in Nanofibers - Li, Na; Qian, Yongfang; Zhang, Zhen; Wang, Ying; Lve, Lihua; Wei, Chunyan (Recent Patents on Nanotechnology, 2020)
Background: The electrospinning and the bubble electrospinning provide facile ways for the fabrication of functional nanofibers by incorporating rutin/hydroxypropyl-β-cyclodextrin inclusion complex (RT/HP-β-CD-IC) in Polyvinyl Alcohol (PVA). Few patents on incorporation of rutin and cyclodextrin in nanofibers has been reported. Objective: The study aimed at increasing the loading amount of rutin in the electrospun nanofibers to obtain ultraviolet resistant property. Methods: Rutin was encapsulated in the cavity of RT/HP-β-CD and formed an inclusion complex. Fourier Transform Infrared Spectroscopy (FTIR) and Differential Scanning Calorimeter (DSC) was used to verify the formation of inclusion complexes. Results: The results showed that the inclusion between rutin and HP-β-CD had been successfully formed. The surface morphologies of nanofibrous membranes were characterized by Scanning Electron Microscope (SEM), which indicated that adding RT/HP-β-CD inclusion complexes had little influence on the morphologies and diameters of the fibers. Ultraviolet resistant results also confirmed the inclusion complex had increased the loading amount in the final nanofibrous mats, and thus had good ultraviolet resistant properties. Conclusion: The formed inclusion complexes had obviously enhanced the loading amount of rutin in electrospun PVA nanofibers, indicating that encapsulation of rutin in the cavity of HP-β-CD is a good way to increase the loading amount.
Keywords: hydroxypropyl-β-cyclodextrin